Assessment of noise from motorway E18 Tønsberg – Sandefjord in Norway - Hosseini , Ehsan (My University, 2022)
In 2014, a motorway was established between Tønsberg and Sandefjord in Norway, with a speed limit of 110 km/h. However, residents living near the E18 have complained of disturbing noise. To increase understanding of the impact of noise generated by the E18, this study employed a series of measurement techniques. Long-term (24-hour) measurements of traffic noise levels were taken on the facades of buildings during the day and night. Short-term (1-hour) measurements of noise levels were taken in surrounding houses using four receiver positions. Additionally, noise mapping and simulated results by SoundPLAN 8.2 were correlated with the short-term monitoring measurements based on two prediction models, RLS-90 and Nord2000, in both winter and summer conditions. The findings suggest that Solbergveien 37 is prone to high sound levels due to temperature inversion. Specifically, sound pressure levels increased by more than 10 dB(A) at 8:00 in the wintertime. The study correlated the measured results with the prediction models at the designated locations. Furthermore, the analysis also focused on the formation of the traffic noise spectrum and its magnitudes at three specific measurement locations.
Keywords: Noise mapping, Nord2000, RLS-90, SoundPLAN, Short-term measurement, Long-term measurement, Traffic noise spectrum, E18